The Influence of molecular Effects on Laser Nd:YAG and Diode on Trichophyton Rubrum fungi using RAPD marker - Marwan A.alkarem A.albaqi; Awatef Saber Jasem; Adnan Fathel A.azawai (Tikrit Journal of Pure Science, 2019)
This study was carried out to assess the morphological and molecular effects of the Nd: yag and Diode (semiconductor) lasers on Trichophyton rubrum Fungi using RAPD marke . Sixty samples of skin patches, nail clippings and parts of hair were collected from infected patients of both sexes (34 males  and 26 females) for the age group (1-60) year of patients who have attended to Tikrit Teaching Hospital. The T.rubrum fungi was the most common among the skin fungi, T.rubrum radiated by using two lasers: the Nd: yag  laser with a wavelength (530) nm and energy (300, 500, 700) mJ and for two times exposing 20 and 30 seconds by six coefficients and control sample, the low-density diode (5 mW) for 3 times 10, 20 and 30 seconds on distance 20 cm with three treatments and a control sample. DNA was extracted from the fungus after direct exposure and after leaving it to grow for a whole generation and then was used to complete RAPD reactions using five primers. The RAPD marker gave excellent results with all primers, It was noted that the exposure of T. rubrum to the Nd: yag and Diode lasers with different cards and times had different effects on DNA and caused significant changes in the RAPD patterns compared with the control group, new bands appear and others disappear. The energy affecting the fungus T.rubrum for the first laser Nd: yag is 500 mj at time 30 sec while the power of the laser Diode was 5 mw at time 20 sec. The results suggested that the diode laser is highly effective and has a great effect on the genetic material of fungi compared with the effect of the first laser. The conclusion that the use of laser can affect DNA of skin fungi and may lead to mutations which means that it can be used in the treatment of skin fungal infections and the RAPD was effective in detecting the effect of laser at the molecular level as a simple, and inexpensive.